Teaching university in a second language: what are the impacts on professors' academic roles and identities?. Issue 3 (3rd July 2019) - Knoerr, Hélène
ABSTRACT: As an officially bilingual institution, the University of Ottawa, the world's largest bilingual French/ English university, requires that some of its professors teach in their second language. Although the needs of students studying in their second language are well documented, very little is known about the experience of professors who teach in their second language. It is therefore important to study the impact of this situation on professors' academic roles and identities in order to understand their needs. We interviewed forty-two University of Ottawa professors who teach or have taught in their second language about the professional, personal, and emotional impact of this situation. We analyzed the interviews using a mixed methodology. This paper presents the preliminary findings from the twenty-one Francophone professors who teach in English regarding the impact of this situation: although their linguistic and cultural identities are not affected, their emotional selves, their academic identities and their professional roles are significantly impacted.